Beauty matters human judgement and the pursuit of new beauties in post-digital architecture - Reisner, Yael; Reisner, Yael; Zeki, Semir; Dijkgraaf, R.; Harman, Graham, 1968-; Dubbeldam, Winka; Ostos, Ricardo de; Pasquero, Claudia; Poletto, Marco; Wiscombe, Tom,|; Colletti, Marjan, 1972-; Rutzinger, Stefan, 1977-; et al. (Profile (Chichester, England), 2019)
Beauty in architecture matters again. This issue of AD posits that after 80 years of aggressive suppression of engagement with aesthetics, the temporarily dormant preoccupation with beauty is back. This is evidenced by a current cultural shift from the supposedly objective to an emerging trust in the subjective. The renewed fascination for aesthetics is supported by new knowledge emanating simultaneously from disparate disciplines. Digital design continues to influence architectural discourse, not only due to changes in manufacturing but also through establishing meaning. The very term 'post-digital' was introduced by computational designers and artists, who accept that digital gains in architectural design ar augmented by human judgement and cognitive intuition. This issue of AD takes an interdisciplinary approach to this re-emerging interest in beauty across neuroscience, neuroaesthetics, mathematics, philosophy and architecture, while discussing the work of the international architects, in both practice and academe, who are generating new aesthetics